New strategy for optimizing wavelength converter placement - Foo, Y. C.; Chien, Su Fong; Low, Andy L. Y.; Teo, C. F.; Lee, Youngseok (Optica Publishing Group, 2005)
This paper proposes a new strategic alternate-path routing to be combined with the particle swarm optimization (PSO) algorithm to better solve the wavelength converters placement problem. The strategic search heuristic is designed to provide network connectivity topologies for the converters to be placed more effectively. The new strategy is applied to the 14-node NSFNET to examine its efficiency in reducing the blocking probability in sparse wavelength conversion network. Computed results show that, when applied to the identical optimization framework, our search method outperforms both the equal-cost multipath routing and traffic-engineering-aware shortest-path routing. (C) 2005 Optical Society of America.